Deterioration of the Soft Lining Materials with the Denture Cleansers - Terao, Takaharu; Inoue, Katsuichiro; Fujii, Kouichi; Kadokawa, Akihiko; Kanie, Takahito; Arikawa, Hiroyuki; Hamano, Tohru (Nihon Hotetsu Shika Gakkai Zasshi, 1992)
Six soft lining materials have been examined (two acrylic, two silicone, one fluoric and one olefin materials) for their viscoelastic properties and surface deterioration caused by using peroxide denture cleansers. All tests have been done on 7.0 mm thickness disk specimens. The viscoelastic properties were investigated using a 10% compression strain and a 40 sec relaxation. From the results, large difference appeared between the various lining materials. 1. The relaxation modulus of the acrylic lining materials was easily deteriorated by the denture cleanser compared with the other lining materials. 2. The cloudiness of the specimen surface and the variation of light reflectivity in the surface of the silicone and olefin lining materials became larger those of the fluoric lining material. 3. Ethanol added as a plasticizer was almost eluted within short period and furthermore the use of denture cleanser increased the elution rate of ethanol.